Early adoption of conservation agriculture practices: Understanding partial compliance in programs with multiple adoption decisions. (January 2018) - Ward, Patrick S.; Bell, Andrew R.; Droppelmann, Klaus; Benton, Tim G.
Abstract: Land degradation and soil erosion have emerged as serious challenges to smallholder farmers throughout Southern Africa. To combat these challenges, conservation agriculture (CA) – a suite of agricultural practices consisting of zero tillage, mulching of crop residues, and intercropping with legumes – is widely promoted as a "sustainable" package of agricultural practices. Despite the many potential benefits of CA, however, adoption remains low. Yet relatively little is known about the decisionmaking process in choosing to adopt CA or any of its constituent practices. This article attempts to fill this important knowledge gap by studying CA adoption in southern Malawi. Unlike what is implicitly assumed when these packages of practices are introduced, farmers view adoption of CA as a series of separate decisions, rather than a single decision. But the adoption decisions need not be wholly independent. We find strong evidence of interrelated decisions, particularly among mulching crop residues and practicing zero tillage, suggesting that mulching residues and intercropping or rotating with legumes introduces a multiplier effect on the adoption of zero tillage.